Vietnam labor market in the context of international integration - Nguyen An Ha (Wieś i Rolnictwo)
This report will introduce and analyze the dynamics of the labor market in Vietnam in the early 21st century, when Vietnam boosts its economic integration into the region and the world. Launched in 1986, the renovation of Vietnam, Doi Moi, which is actually a reform of the economy, transition from the centralized planning economy to the market one, has gained great achievements. Along with the formation and development of for goods and services market, capital and financial markets, real estate market, science and technology market, that of labor market in Vietnam shows the effort of market-oriented innovation, from awareness to the building of legal system, policy making and application in practice. In the late twentieth century, the labor market was established and developed on the basis of reform policies of the Party and State to build a multi-sector economy that is run under the market mechanism with the socialist-oriented management of the State. Importantly, Doi Moi also means the open of the economy to the regional and international one, with policies to attract foreign investors to come. Foreign investment is a very important factor to construct the labor market in Vietnam that shows a strong shift of people, especially young people, from the rural to the urban, particularly industrial zones located in industrialized provinces in both the North and the South.